2020
DOI: 10.1186/s12860-020-00270-5
|View full text |Cite
|
Sign up to set email alerts
|

CHD9 upregulates RUNX2 and has a potential role in skeletal evolution

Abstract: Background: Changes in gene regulation are widely recognized as an important driver of adaptive phenotypic evolution. However, the specific molecular mechanisms that underpin such changes are still poorly understood. Chromatin state plays an essential role in gene regulation, by influencing the accessibility of coding loci to the transcriptional machinery. Changes in the function of chromatin remodellers are therefore strong candidates to drive changes in gene expression associated with phenotypic adaptation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…A previous study also revealed that PTE inhibited inflammation and apoptosis in mouse models of pulmonary fibrosis (37). ALP has been considered to be an early osteogenic marker, whilst RUNX2 regulates the differentiation of pluripotent stem cells into osteoblasts (38).…”
Section: Discussionmentioning
confidence: 94%
“…A previous study also revealed that PTE inhibited inflammation and apoptosis in mouse models of pulmonary fibrosis (37). ALP has been considered to be an early osteogenic marker, whilst RUNX2 regulates the differentiation of pluripotent stem cells into osteoblasts (38).…”
Section: Discussionmentioning
confidence: 94%
“…The bill of billfishes results from the specialization of the upper jaw bone. Previous studies have found that the gene runx2 was a major driver of craniofacial evolution in mammals, while chd9 was found to be a potential regulator for runx2 ( Newton and Pask 2020 ). Interestingly, among the two CNEs with billfish-specific deletions, one (UCE-1582) is located 172 kb upstream of chd9 and they are also in the same TAD ( fig.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, some, such as CHD1, are required for RNAPII transcription ( Krogan et al 2002 ; Simic 2003 ; Srinivasan et al 2005 ; Warner et al 2007 ; Skene et al 2014 ; Dieuleveult et al 2016 ; Baumgart et al 2017 ) and play a role in transcription initiation ( Lin et al 2011 ) and in RNAPII-directed turnover of promoter-proximal nucleosomes, promoter escape, and subsequent elongation and splicing ( Sims et al 2007 ; Skene et al 2014 ). Similarly, mounting evidence shows that mammalian CHD2 ( Rom et al 2019 ), CHD6 ( Lutz et al 2006 ), CHD8 ( RodrĂ­guez-Paredes et al 2009 ; Ceballos-ChĂĄvez et al 2015 ), and CHD9 ( Shur et al 2006a ; Lee and Stallcup 2017 ; Alendar et al 2020 ; Newton and Pask 2020 ; Yoo et al 2020 ) potentiate transcription of distinct target genes in diverse cell types. CHD enzymes also contribute to transcriptional repression, best exemplified by the concerted action of chromatin remodeling and histone deacetylase catalytic subunits of the NuRD complex, which generally leads to the generation of hypoacetylated, densely packed chromatin ( Lai and Wade 2011 ) and facilitates PRC2-mediated silencing of target genes in ESCs ( Reynolds et al 2012 ).…”
Section: Chromatin Organization and Transcriptional Regulationmentioning
confidence: 99%